Juridical Analysis Of Settlement Of Land Disputes Through Decisions Of Customary Institutions - Rineke Sara; Zudan Arief Fakrulloh; Asriadi Asriadi (Publikasi Indonesia, 2023)
The land is a natural resource that has a very important role because the land is needed by humans for various kinds of life interests such as living, farming, trying, and so on. The policy for the development of the land sector in Indonesia is essentially rooted in the provisions of the 1945 Constitution Article 33 paragraph (3) which reads